Impact of a medication reconciliation care bundle at hospital discharge on continuity of care: A randomised controlled trial. Issue 8 (13th May 2021) - Bouchand, Frédérique; Leplay, Céline; Guimaraes, Ricardo; Fontenay, Sarah; Fellous, Lesly; Dinh, Aurélien; Deconinck, Laurène; Sénard, Olivia; Matt, Morgan; Michelon, Hugues; Perronne, Christian; Salomon, Jérôme; et al.
Abstract: Objective: To compare the impact of a care bundle including medication reconciliation at discharge by a pharmacist versus standard of care, on continuity of therapeutic changes between hospital and primary care and outcome of patients, within 1 month after discharge. Methods: Randomised controlled trial in 120 adult patients with at least one chronic disease and three current medications before admission, hospitalised in an infectious disease department of a tertiary hospital and discharged home. Patients were randomly assigned (1:1) to receive a discharge care bundle including medication reconciliation, counselling session and documentation transfer to primary care physician (PCP) (intervention group) or standard of care (control group). Primary outcome was the proportion of in‐hospital prescription changes, not maintained by the PCP, 1 month after discharge. Secondary outcome measures included the proportion of patients experiencing early PCP's consultation, hospital readmissions or adverse reactions within 1‐month postdischarge and cost of discharge prescriptions. Results: Baseline characteristics were comparable between the two groups. One month after discharge, the proportion of in‐hospital prescription changes, not maintained by the PCP, was 11% in the intervention group versus 24% in the control group ( P  = .007). The median delay before PCP's consultation was longer in the intervention group (30.5 vs 19.5 days, P  = .013), there were fewer patients readmitted to hospital (3.4% vs 20.7%, P  = .009, odds ratio (OR) = 0.13 [0.02‐0.53]) and fewer patients who suffered from adverse drug reaction (7.0% vs 22.8%, P  = .04, OR = 0.26 [0.07‐0.78]). Conclusion: This care bundle resulted in the reduction of treatment changes between hospital discharge and primary care.